2016
DOI: 10.5194/soil-2-351-2016
|View full text |Cite
|
Sign up to set email alerts
|

Thermal alteration of soil physico-chemical properties: a systematic study to infer response of Sierra Nevada climosequence soils to forest fires

Abstract: Abstract. Fire is a common ecosystem perturbation that affects many soil properties. As global fire regimes continue to change with climate change, we investigated thermal alteration of soils' physical and chemical properties after they are exposed to a range of temperatures that are expected during prescribed and wildland fires. For this study, we used topsoils collected from a climosequence transect along the western slope of the Sierra Nevada that spans from 210 to 2865 m a.s.l. All the soils we studied wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 56 publications
7
35
0
Order By: Relevance
“…SOM is vulnerable to temperatures, while soil minerals are only affected at much higher temperatures (Araya et al, 2016). In addition, all of the soils in our study are characterized by low clay content and low concentration of reactive minerals, but they have a high concentration of SOM, especially in the topsoil, leading to strong relationships between SOM concentrations and soil physical properties.…”
Section: Implication Of Som Changes With Heatingmentioning
confidence: 91%
See 3 more Smart Citations
“…SOM is vulnerable to temperatures, while soil minerals are only affected at much higher temperatures (Araya et al, 2016). In addition, all of the soils in our study are characterized by low clay content and low concentration of reactive minerals, but they have a high concentration of SOM, especially in the topsoil, leading to strong relationships between SOM concentrations and soil physical properties.…”
Section: Implication Of Som Changes With Heatingmentioning
confidence: 91%
“…We selected four forested sites that are likely to experience forest fires and a fifth lowerelevation grassland site. The thermal alterations in bulk soil physical and chemical properties from the same study soils were previously reported in Araya et al (2016).…”
Section: Study Site and Soil Descriptionmentioning
confidence: 92%
See 2 more Smart Citations
“…The loss of vegetation that would otherwise stabilize soil in eroding landform positions, along with increased soil hydrophobicity after moderate severity fires leaves soil more directly exposed to weathering and erosion (DeBano, 2000;Shakesby et al, 2000;Larsen et al, 2009). Fires can also raise soil pH, alter cation exchange capacity, and change the soil organic matter (SOM) composition (Giovannini et al, 1988;DeBano, 1991;Certini, 2005;Liang et al, 2006;Araya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%